Derecho y política agrarios y agroalimentarios - Pastorino, Leonardo Fabio (2017)
The specifics of agricultural activity entails a necessity to adopt for it a special regulation in the form of agricultural law. The performance of agricultural activity is a contributory factor to co-occurrence of a number of relationships shaping the contemporary agricultural structure which in the event of incompliance with the economic, social or environmental goals leads to a situation which Antonio Vivanco termed ‘structural deficiencies’. Their appearance sometimes enforces State intervention which then frequently means adoption of new legal instruments in the sphere of agricultural law. A look at this phenomenon globally from the perspective of the production chain leads to a conclusion that it refers to the agro-industrial and agro-food sectors, which means that a focus is put on the inter-relations in the production chain and especially on the relationships between agricultural produce markets and agricultural producers. The aim of this paper is to describe these issues on the example of Argentina. An analysis is also made on the usually disadvantageous situation of the primary producers in comparison with the other participants of the production chain. The need for a thought on the possibility of classifying agricultural production as one of the elements safeguarding public order has been emphasised.